fbpx
calculus online - Free exercises and solutions to help you succeed!

Equations- Factorization of a polynomial equation – Exercise 5613

Exercise

Factor the polynomial equation

2x^3+5x^2-2x-5=0

Final Answer


(2x+5)(x-1)(x+1)=0

Solution

2x^3+5x^2-2x-5=

We extract a common factor from the first two expressions:

=x^2(2x+5)-2x-5=

We arrange the last two expressions to be exctly as the expression in parentheses:

=x^2(2x+5)-(2x+5)=

Once again we extract a common factor – this time the expression in parentheses:

=(2x+5)(x^2-1)=

We break down the second factor using Short Multiplication Formulas (third formula) and get the factorizing:

=(2x+5)(x-1)(x+1)

Share with Friends

Leave a Reply